Democracy in Confucianism - TAN, Sor-hoon (Institutional Knowledge at Singapore Management University, 2012)
Confucianism’s long historical association with despotism has cast doubts on its compatibility with democracy, and raise questions about its relevance in contemporary societies increasingly dominated by democratic aspirations. “Confucian democracy” has been described as a “contradiction in terms” and Asian politicians have appropriated Confucianism to justify resistance to liberalization and democratization. There has been a lively debate over the question of whether democracy can be found in Confucianism, from ancient texts such as the Analects and Mencius, to Confucian institutions such as those recommended by Song dynasty Huang Zongxi. Philosophers have examined similarities and differences between Western ideas, such as autonomy, liberty, and rights, that are central to democratic theories on the one hand and Confucian ideas of virtue, ren (humaneness), yi (appropriateness), li (rite), zhi (wisdom), exemplary person and authority. Scholars have studied the biographical accounts of prominent Confucians to understand the Confucian ideal person and society. Works arguing that there are elements of democracy in Confucianism, or that some Confucian ideas could provide the basis for a contemporary Confucian democracy, differ in the kind of democracy they choose as models. Liberal democracy was the model of earlier works; with increasing criticisms of liberal democracy in the past decades, a growing number of works arguing for Confucian democracy seek alternatives to liberal democracies, many proposing some kind of communitarian democracy as having affinity with the Confucian philosophical orientation. Besides conceptions of democracy that view it in terms of political systems, Dewey’s conception of democracy as the idea of community and primarily a moral ideal has also inspired attempts to reconstruct Confucian democracy.